MAPPING THE GOOD FAITH PRINCIPLE IN INTERNATIONAL INVESTMENT ARBITRATION: ASSESSMENT OF ITS SUBSTANTIVE AND PROCEDURAL VALUE - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
International investment cases show the frequent use of good faith arguments by both investors and respondent states. These cases also illustrate how parties and tribunals tend to conceptualize the good faith principle which has become an important rule of international investment law. This article will explore recent trends in order to assess the importance of this argument for both parties and at different stages of the proceeding. This article will also provide an overview of responses given by the tribunals faced with good faith arguments. Whereas claimants have traditionally relied on this concept to argue the breach of fair and equitable treatment and legitimate expectations, recent cases such as Inceysa, Phoenix and TSA Spectrum, indicate a new defence strategy for respondent states. Given the fact that investment tribunals have shown willingness to treat the good faith principle as autonomous and as a self-standing standard, the possibilities for respondent states have increased. Respondent states can rely on good faith to deny the right of claimants to seize the tribunal (Article 41(5) of the ICSID Rules), to challenge the jurisdiction of the tribunal or admissibility, to contest the right of the claimant to have a decision in its favour, or to challenge the right to compensation.